The emperical analysis of monetary model to the exchange rate determination : Remainder of title Malaysia ringgit, Singapore dollar and Indonesia rupiah cases - Erlambang, Tanza (1999)
This study concerned with an empirical analysis and validation of monetary model to determine exchange rate of 3 ASEAN countries (Malaysia, Indonesia and Singapore) against major developed country currencies, namely USA, Japan, Germany and United Kingdom. Based on 3 different statistic test results ( aunit root test, Johansen cointegration test and single equation diagnostic test), it is could be concluded that monetary model is a valid framework to analyze movement of Malaysia Ringgit to Japan Yen, and Movement of Singapore Dollar to British Pound, Germany Mark, US Dollar and Japan Yen.